Association between clinical characteristics and pain relief in patients with axial spondyloarthritis treated with non-steroidal anti-inflammatory drugs - Shiyi Deng,; Yi He,; Sisi Deng,; Erwei Sun,; Li Li, (Archives of Rheumatology, 2022)
Objectives: The aim of this study was to evaluate pain relief in axial spondyloarthritis (axSpA) patients treated with non-steroidal anti-inflammatory drugs (NSAIDs) and to investigate the relation of the demographic, clinical, and psychological characteristics with pain relief. Patients and methods: Between February 2017 and December 2019, a total of 94 patients (61 males, 33 females; mean age: 28.3±8.1 years; range, 14 to 54 years) who were diagnosed with axSpA and treated with NSAIDs were included. The patients were assessed at baseline and at three months. A reduction of 30% in the Numeric Rating Scale (NRS) indicates a clinically meaningful improvement. The patients were divided into the relief group (≥30% improvement in NRS) and non-relief group (<30% improvement). Potential influential factors for pain relief such as neuropathic pain (NP), disease activity, function, pain catastrophizing, and pain self-efficacy were assessed. The relationship between patients’ characteristics and pain relief was analyzed. Results: Seventy-two (76.6%) patients achieved pain relief. These patients had significantly higher baseline erythrocyte sedimentation rate, C-reactive protein, and lower percentage of NP. There was no significant difference between the two groups in function, pain catastrophizing, and pain self-efficacy. Multiple logistic regression analysis revealed that patients with NP were less likely to achieve pain relief (odds ratio [OR]: 3.531, 95% confidence interval [CI]: 1.155-10.789; p=0.027). Conclusion: Pain relief is still insufficient in some axSpA patients, despite the administration of NSAIDs. The presence of NP is significantly associated with poor pain relief. Alternative medications instead of NSAIDs are needed to achieve optimal pain relief, when NP is diagnosed.